FANDA YARATILGAN INNOVATSIYALAR, TAJRIBA VA YUTUQ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
Innovation in science is the process of introducing highly novel and useful elements of investigation into a scientific community Innovations in Science is intended for news, more comfortable life and putting ideas into action. In current days scientist surfe into the field of innovations attracting students and clever people to a wide variety of scientific fields such as physics, molecular biology, chemistry, biochemistry, astronomy, engineering, neuroscience, immunology, psychology, and earth science. Loads of experience through hardship and learning or exploring life has brought to success in creation of innovations in science. And today we all are utilizing some sort of innovations has been made so far. In this article, path of created innovations, general conception about that sphere will be submitted as well as experience and gained success will be discussed.
Keywords: Scientific innovation, elements, as physics, molecular biology, chemistry, biochemistry, astronomy, engineering, neuroscience, immunology, psychology, and earth science.